Determination of Angiopoietin Like Protein-4 Levels and Some Parameters in Iraqi Patients with Type 2 Diabetes Mellitus. - Wadood, Shatha Abdul; Saihood, Yahya D; Mohammed, Zahraa J (Al-Nahrain Journal of Science, 2018)
A. Background: Diabetes initiates the thrombotic complications of atherosclerosis through changing the function of endothelial cells, smooth muscle cells and platelets. Also insulin resistance, hyperglycemia and dyslipidemia can lead to arterial atherosclerosis in diabetic patients. Angiopoietin like protein- 4 (ANGPTL4) is a multifunctional protein involved in lipid regulation, energy metabolism, angiogenesis, and inflammation. Its expression is stimulated in liver, heart, muscle and adipose tissue, during the acute phase response. C-reactive protein directly induces the expression of adhesion molecules by endothelial cells. Also recruiting monocytes into the vessel wall are triggered by the expression of specific chemokines particularly monocyte chemoattractant protein-1 (MCP-1), all these processes induce the risk of atherosclerotic complications with type 2 diabetes mellitus (T2DM). B. Aim of this study: To study the role of ANGPTL4 in T2DM patients with and without atherosclerosis risk factor (dyslipidemia), and to demonstrate the relationship of ANGPTL4 with inflammatory process.